2012
DOI: 10.1007/s11999-011-2211-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Primary or Secondary Chondrocalcinosis Influence Long-term Survivorship of Unicompartmental Arthroplasty?

Abstract: Our findings show chondrocalcinosis does not influence progression and therefore is not a contraindication to UKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
3
23
0
4
Order By: Relevance
“…The presence of CPPD crystals at the time of knee surgery was not associated with decreased ultimate knee ROM or lower KS scores after surgery. The similarities of functional disabilities between patients with chondrocalcinosis as a group to those without chondrocalcinosis are consistent with other published reports [5,16]. Viriyavejkul et al [16] compared the characteristics of patients with and without CPPD undergoing TKA for osteoarthritis and reported no differences in age at pain onset, time to surgery, difficulty in performing daily functions, or history of prior joint inflammation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The presence of CPPD crystals at the time of knee surgery was not associated with decreased ultimate knee ROM or lower KS scores after surgery. The similarities of functional disabilities between patients with chondrocalcinosis as a group to those without chondrocalcinosis are consistent with other published reports [5,16]. Viriyavejkul et al [16] compared the characteristics of patients with and without CPPD undergoing TKA for osteoarthritis and reported no differences in age at pain onset, time to surgery, difficulty in performing daily functions, or history of prior joint inflammation.…”
Section: Discussionsupporting
confidence: 83%
“…There is little published information on the effect of chondrocalcinosis on TKA survivorship. Hernigou et al [5] reported on a series of 234 unicompartmental knee arthroplasties and compared the failure rates of patients with and without chondrocalcinosis and found no differences in the 15-year cumulative survivorship of the implants. Therefore, CPPD crystal deposition is not a poor predictor for TKA survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…3), may reflect differences in indications for surgery and surgical technique. It has also been shown that survivorship is improved by surgeons in centres performing more operations per year [11], reflecting greater experience with the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited number of series, the literature does not support this theoretical disadvantage. Hernigou et al 55 proved the incorrectness of this theory; only 11% of their patients showed progression of OA of the other compartment, which is equivalent or less than UKA knees without chondrocalcinosis 43. Another report by the Oxford Group showed no significant difference in survival between patients with radiological chondrocalcinosis undergoing medial UKA and controls without chondrocalcinosis.…”
Section: Current State Of the Artmentioning
confidence: 99%
“…Chondrocalcinosis, deposition of calcium pyrophosphate crystals in fibrocartilage and hyaline cartilage, is commonly seen in knees with OA 55. It is believed that chondrocalcinosis leads to a more aggressive form of OA, potentially leading to accelerated contralateral compartment OA following UKA.…”
Section: Current State Of the Artmentioning
confidence: 99%